A choice considered [large type] - Peterson, Tracie (Peterson, Tracie. Heart of Cheyenne., 2024)
"Melody Doyle has spent years following her father across the country as the trans-continental railroad is built. When she announces her desire to settle down in Cheyenne, her father presents her with an unconventional challange: he will allow her to stay if she finds a husband before his departure. Charles Decker, heir to a banking dynasty, has been sent west by his father to manage the family's new bank. When his friendship with Melody blossoms, he's drawn to this remarkable woman who defies conventions. Will he be able to come to terms with his feelings for her and confront the desires of his heart before it's too late? --